KONSEP TASWIYAH AL-NAFS DALAM PENGEMBANGAN PRIBADI MANUSIA - Hamdie, Ilham Masykuri (Khazanah: Jurnal Studi Islam dan Humaniora, 2017)
The manifestation of human superiority as ‘ahsan al-taqwim’ can be interpreted as the process of developing the level of "inner aspect" of the human called ‘nafs’. In this context the dimensions of ‘nafs’ or soul that exists in the human still leaves a long discussion to be examined further for the purposes of parsing, forecasting and controlling human behaviour, either individually or in groups, both in relation to the field of ‘da'wah’ or education, for the benefit of mobilizing society in nation-building. Therefore, a research on the concept of ‘taswiyah al-nafs’ in the development of the human person becomes important to be conducted. The results has shown that in the process of ‘taswiyat al-nafs’, besides having the freedom of will and choosing between ‘fujur’ or ‘taqwa’ tendencies, man also have the moral responsibility implied as a subtle command and indirectly to take and choose ‘taqwa’. It is because, the essence of ‘taqwa’ is the mastery, control and self-preservation of ‘al-ahwa'. ‘Taqwa’ as an effort of mastery, control and self-preservation is a prerequisite for the process of human development as a civilized being. The effort is essentially a process of an endless human self-development to reach the ideal of ‘insan kamil’—a perfect man reflecting the names and attributes of God—‘al-asma'ul-husna’.